Sistem Informasi Pelayanan Masyarakat (Sipemas) Di Kantor Lurah Pipa Reja Palembang - Amalia, Rianti; Sanmorino, Ahmad; Ariati, Nining (Jurnal Ilmiah Informatika Global, 2025)
Efficient and transparent public services are an essential need for communities in today's digital era. This study aims to design and develop a Public Service Information System (SIPeMas) at the Pipa Reja Palembang Village Office to overcome service problems that are still carried out traditionally. The main challenges faced include slow service processes, lack of clarity in procedures, difficulty integrating data, and low levels of public satisfaction. The research method used is a system development approach with the agile method, which includes steps for data collection, needs analysis, system design, implementation, and testing. The system developed includes online service registration, data integration between types of services, information on procedures and requirements, notification of application status, and monitoring and evaluation of service performance. The types of services integrated into the system include making marriage introduction letters, certificates of poverty, certificates of not having a house, death certificates, domicile certificates, and certificates of not being married. This research focuses on the Pipa Reja Palembang Village area as a case study. Additionally, this system provides ongoing assistance to the village in monitoring and evaluating service performance. It is expected that SIPeMas can be an example of a service information system for other government agencies, as well as encourage the improvement of the quality of public services through the use of information technology.